PENERAPAN EKOWISATA DI DESA TANJUNG BELIT SEBAGAI KAWASAN PENYANGGA SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING - Pasaribu, Sri Sagitari; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study analyzes the implementation of ecotourism in Tanjung Belit Village, Riau, as a critical buffer zone for the Bukit Rimbang Bukit Baling Wildlife Sanctuary. Employing a qualitative approach through in-depth interviews, participant observation, and document analysis, this research explores the potential, challenges, and impacts of ecotourism on conservation and the well-being of the local community. The findings reveal that Tanjung Belit Village possesses significant natural and cultural attractions, yet the implementation of ecotourism remains constrained by limited infrastructure, lack of community participation, and suboptimal promotional strategies. Nevertheless, ecotourism has contributed to improving the local economy, raising conservation awareness, and protecting ecosystems, particularly through local wisdom practices such as Lubuk Larangan. Keywords: Ecotourism, Buffer Zone, Conservation, Community Participation, Sustainable Tourism.